The Relationship of Self-Efficiency and Social Support with Adolescent Bullying at Junior High School 2 Sepatan - Arini, Dwi; Novianti, Evin (UIMA Press, 2021)
Background: Adolescents face the problem of bullying, they need social support from those around them to have confidence in their abilities. Purpose: The purpose of this study was to determine the relationship between self-efficacy and social support with bullying in adolescents at Junior High School 2 Sepatan, Tangerang Regency. Methods: The research design is cross-sectional using the spearman correlation test to analyze the relationship between variables. The sampling technique was simple random sampling with 127 respondents. The instrument uses a self-efficacy questionnaire, Multidimensional Scale of Perceived Social Support, and The revised Olweus Bully or Victim Questionnaire. Results: There is a significant relationship between self-efficacy and bullying (p-value 0.031) and there is a significant relationship between social support and bullying (p-value 0.001). Conclusion: There is a relationship between self-efficacy and social support for victims of bullying in adolescents. This study is also useful for parents that teenagers need support in getting through the effects of bullying.